2009
DOI: 10.1007/s00038-009-8054-0
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization influences dietary habits of Cypriot children: the CYKIDS study

Abstract: The minor differences relating the dietary patterns to the place of residence reflect the changes in eating habits and the abandonment of the traditional Mediterranean diet, which may be attributed to the nutrition transition and urbanization phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 20 publications
5
35
0
2
Order By: Relevance
“…28 Many of the above-mentioned studies on the Mediterranean diet in children described the cross-sectional association with health outcomes such as asthma 41 or overweight. 42 Most were set up in a Mediterranean country such as Greece, [42][43][44] Cyprus, 45,46 Spain 47,48 and Turkey. 49 A few studies were based on children living in a non-Mediterranean country like UK 22 and Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…28 Many of the above-mentioned studies on the Mediterranean diet in children described the cross-sectional association with health outcomes such as asthma 41 or overweight. 42 Most were set up in a Mediterranean country such as Greece, [42][43][44] Cyprus, 45,46 Spain 47,48 and Turkey. 49 A few studies were based on children living in a non-Mediterranean country like UK 22 and Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicated a low to moderate adherence to the Mediterranean diet, a finding that is in line with previous data from Greece and other Mediterranean countries. [6][7][8]20,21 It follows that teenagers, despite being generally well informed about healthy eating, do not often translate this knowledge into their daily lives. Other studies have also shown that nutrition label reading and food education do not translate into healthier diet in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse cenário, destaca-se o hábito de assistir à televisão ou o uso de jogos eletrônicos pela população, que por sua vez, não só inibe a realização de atividades físicas como também expõe o indivíduo a um volume cada vez maior de publicidade de alimentos 6,7,8 . No Brasil, quase toda população (99%) possui ao menos um aparelho de televisão em casa (Instituto Brasileiro de Opinião Pública e Estatística.…”
Section: Introductionunclassified